1996
DOI: 10.1038/383522a0
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of malaria in α-thalassaemic children

Abstract: The alpha+-thalassaemias are the commonest known human genetic disorders, affecting up to 80 per cent of some populations. Although there is good evidence from both epidemiological and clinical studies that these gene frequencies reflect selection by, and protection from, malaria, the mechanism is unknown. We have studied the epidemiology of malaria in childhood on the southwestern Pacific island of Espiritu Santo in Vanuatu and here we report that, paradoxically, both the incidence of uncomplicated malaria an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
163
3
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(174 citation statements)
references
References 20 publications
5
163
3
3
Order By: Relevance
“…It is always possible that this distribution simply reflects the fact that ␣ + thalassemia was introduced to these island populations by founders from the mainland and that the gene frequency was gradually diluted as they migrated south. However, this explanation was excluded by the finding that the molecular forms of ␣ + thalassemia and the restriction fragment length polymorphisms associated with them in the island populations are completely different from those of the Asian mainland (Flint et al 1986 (Williams et al 1996). In a large cohort of babies of different ␣-globin genotypes, followed carefully over the first years of life, it was found that those homozygous for ␣ + thalassemia have a higher frequency of both Plasmodium vivax and P. falciparum malaria in the first 2 years of life, after which this effect is not seen.…”
Section: Malariamentioning
confidence: 99%
“…It is always possible that this distribution simply reflects the fact that ␣ + thalassemia was introduced to these island populations by founders from the mainland and that the gene frequency was gradually diluted as they migrated south. However, this explanation was excluded by the finding that the molecular forms of ␣ + thalassemia and the restriction fragment length polymorphisms associated with them in the island populations are completely different from those of the Asian mainland (Flint et al 1986 (Williams et al 1996). In a large cohort of babies of different ␣-globin genotypes, followed carefully over the first years of life, it was found that those homozygous for ␣ + thalassemia have a higher frequency of both Plasmodium vivax and P. falciparum malaria in the first 2 years of life, after which this effect is not seen.…”
Section: Malariamentioning
confidence: 99%
“…For instance, selection of α-thalassaemia genes by malaria has been shown to result from an increased susceptibility to uncomplicated infection with Plasmodium vivax early in life which, by hastening acquisition of immunity, leads subsequently to protection against lethal infections with P. falciparum. 33,34 However, no selective advantage of the low MBP producing variants yet has been clearly demonstrated in African populations. In extensive studies of malaria, HBV persistence, and tuberculosis in Gambia, no evidence was found to link MBP variants either to resistance or susceptibility to infection.…”
Section: Allele 2 Hy-ly-lx-ly-g57e Ly-g54d Lx-r52cmentioning
confidence: 99%
“…The latter, therefore, remains largely undefined. A further feature of these genetic studies is that they have used a broad spectrum of possible measures of resistance, including parasite density (8)(9)(10)(18)(19)(20)(21), severity of symptoms (7,15,(22)(23)(24)(25)(26)(27), and immune responsiveness (16,17,28). As there is no real consensus as to which measures are good indicators of protection from disease, it can be argued that the importance of host genetics is most meaningfully assessed by observing the frequency and severity of clinical disease, as reported by the patient, in the field.…”
mentioning
confidence: 99%